Developing tactics for listening - Richards, Jack C (Oxford University Press, 1997)
Developing tactics for listening is the second level of a three level listening series for beginning through intermediate learners. The key features of this teacher's book includes: detailed instructions to prepare, present and check each activity; skill focus provided for each activity; cultural notes; optional extension activites for listening; optional speaking activities; vocabulary lists for each activity; photocopiable tapescripts for the Audio Program and answer key for the student book